2009
DOI: 10.3923/pjbs.2009.1581.1584
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antiproliferative Effect of Infusions and Essential Oil of Aloysia gratissima

Abstract: Aloysia gratissima is used in Brazilian folk medicine for the treatment of digestive and respiratory diseases. The infusions (6 and 24 g L-1) and essential oils (0.25%, on ethanol) were prepared and we used groups of five Allium cepa bulbs for each treatment. A total of 2500 cells per treatment were analyzed and the mitotic indexes were calculated. The antiproliferative effect of infusions and essential oils of Aloysia gratissima on the Allium cepa (onion) cell cycle was evaluated using the leaves of studied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This perennial plant is common on the southern coastal plain of Sonora and is endemic to coastal thorn scrub. It is important to mention that some species of the Aloysia genus have shown anti-proliferative and antibacterial activity (Hister, Laughinghouse, Da Silva, Do Canto Dorrow & Tedesco, 2009;Vandresen et al, 2010). The Aloysia gratisima essential oil and infusions are responsible for inducing apoptosis on Allium cepa cells (Hister et al, 2009), while an Aloysia citriodora essential oil showed antiproliferative activity against P815, MCF7 y VERO cancerous cell lines with IC 50 values of 6, 34 and 32 µg/mL, respectively (Oukerrou et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This perennial plant is common on the southern coastal plain of Sonora and is endemic to coastal thorn scrub. It is important to mention that some species of the Aloysia genus have shown anti-proliferative and antibacterial activity (Hister, Laughinghouse, Da Silva, Do Canto Dorrow & Tedesco, 2009;Vandresen et al, 2010). The Aloysia gratisima essential oil and infusions are responsible for inducing apoptosis on Allium cepa cells (Hister et al, 2009), while an Aloysia citriodora essential oil showed antiproliferative activity against P815, MCF7 y VERO cancerous cell lines with IC 50 values of 6, 34 and 32 µg/mL, respectively (Oukerrou et al, 2017).…”
mentioning
confidence: 99%
“…It is important to mention that some species of the Aloysia genus have shown anti-proliferative and antibacterial activity (Hister, Laughinghouse, Da Silva, Do Canto Dorrow & Tedesco, 2009;Vandresen et al, 2010). The Aloysia gratisima essential oil and infusions are responsible for inducing apoptosis on Allium cepa cells (Hister et al, 2009), while an Aloysia citriodora essential oil showed antiproliferative activity against P815, MCF7 y VERO cancerous cell lines with IC 50 values of 6, 34 and 32 µg/mL, respectively (Oukerrou et al, 2017). Based on these studies "Mariola" could have a potential anti-proliferative activity against cancer cell lines, however, this plant has only been used as a treatment for cold, fever, and stomach aches (Yetman & Denver, 2002).…”
mentioning
confidence: 99%